Hierarchical macro-nanoporous metals for leakage-free high-thermal conductivity shape-stabilized phase change materials. (1st July 2020) - Grosu, Yaroslav; Zhao, Yanqi; Giacomello, Alberto; Meloni, Simone; Dauvergne, Jean-Luc; Nikulin, Artem; Palomo, Elena; Ding, Yulong; Faik, Abdessamad
Highlights: Hierarchical macro-nanoporous metal for shape-stable, leakage-free, conductive PCMs. Anti-leakage due to nanopores and high energy density due to macropores (90 vol%) Concept proven for hierarchical macro-nanoporous copper impregnated with paraffin. A threefold enhancement of thermal conductivity for Cu + paraffin vs paraffin. Approach is suitable for battery pack thermal management as shown by CFD modeling. Abstract: Impregnation of Phase Change Materials (PCMs) into a porous medium is a promising way to stabilize their shape and improve thermal conductivity, which are essential for thermal energy storage and thermal management of small-size applications, such as electronic devices or batteries. However, in these composites a general understanding of how leakage is related to the characteristics of the porous material is still lacking. As a result, the energy density and the antileakage capability are often antagonistically coupled. In this work we overcome the current limitations, showing that a high energy density can be reached together with superior anti-leakage performance by using hierarchical macro-nanoporous metals for PCMs impregnation. By analyzing capillary phenomena and synthesizing a new type of material, it was demonstrated that a hierarchical trimodal macro-nanoporous metal (copper) provides superior antileakage capability (due to strong capillary forces in nanopores), high energy density (90 vol% of PCM load due to macropores) and improves the charging-discharging kinetics, due to a three-fold enhancement of thermal conductivity. It was further demonstrated by CFD simulations that such a composite can be used for thermal management of a battery pack and, unlike pure PCM, it is capable of maintaining the maximum temperature below the safety limit. The present results pave the way for the application of hierarchical macro-nanoporous metals for high-energy density, leakage-free, and shape-stabilized PCMs with enhanced thermal conductivity. These innovative composites can significantly facilitate the thermal management of compact energy systems such as electronic devices or high-power batteries by improving their efficiency, durability, and sustainability.